Biogenic synthesis of aromatic cardamom-wrapped zinc oxide nanoparticles and their potential antibacterial and mosquito larvicidal activity: An effective eco-friendly approach. Issue 6 (December 2020) - Vinotha, Viswanathan; Yazhiniprabha, Mariappan; Raj, Daniel Selva; Mahboob, Shahid; Al-Ghanim, Khalid A.; Al-Misned, Fahad; Govindarajan, Marimuthu; Vaseeharan, Baskaralingam
Graphical abstract: Highlights: Aromatic Elettaria cardamomum ( Ec ) plant-assisted Zinc oxide nanoparticles (ZnO NPs) were synthesized. The synthesized Ec -ZnO NPs were characterized by UV, XRD, FTIR, and TEM. Ec -ZnO NPs show potent antioxidant activity. Ec -ZnO NPs show antibacterial and antibiofilm activity against bacterial pathogens. Ec -ZnO NPs show productive larvicidal activity against Aedes aegypti and Culex tritaeniorhynchus . Abstract: In the current study, Elettaria cardamomum ( Ec ) seed extract–assisted zinc oxide nanoparticles (ZnO NPs) were synthesized by a secure co-precipitation method and characterized through UV–vis, XRD, FTIR, SEM and TEM. The surface plasmon resonance of Ec -ZnO NPs was distinguished at 373 nm. The XRD pattern authenticates the crystalline nature and matches with JCPDS file No. 36-1451. The result acquired from the FTIR spectrum conveyed the potential biomolecules that take place in the Ec -ZnO NPs by sharp express peaks at 3472.30, 1416.81, 1573.95, 1557.02, and 848.25 Cm −1 . SEM and TEM images make known the homogenous spherical form and average size (18.72 nm) of Ec -ZnO NPs, respectively. The Ec -ZnO NPs have better antioxidant activity at 100 μg/ml concentration than Ec seed extract. Additionally, the Ec -ZnO NPs were encompassed with enhanced antibiofilm activity at 100 μg/ml concentration against four different bacteria Enterococcus faecalis, Staphylococcus aureus, Pseudomonas aeruginosa, and Proteus vulgaris . Among them, Gram-negative bacteria were more susceptible to Ec -ZnO NPs. Moreover, when compared to Ec seed extract, the Ec -ZnO NPs was highly potential agent against Aedes aegypti (LC50 = 13.27 μg/ml, LC90 = 25.36 μg/ml) and Culex tritaeniorhynchus (LC50 = 15.09 μg/ml, LC90 = 29.70 μg/ml). Compare to Cx. tritaeniorhynchus, Ae. aegypti was more susceptible to Ec -ZnO NPs. Thus, the Ec -ZnO NPs can probably utilize to reduce the bacterial biofilm in the discipline of biomedical and pharmaceutics and as well as remarkable larvicidal agent to the constraint of mosquito vectors.